2014
DOI: 10.7314/apjcp.2014.15.16.6939
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine Induces Autophagic Cell Death in Oral Cancer Cells via Akt and ERK Pathways

Abstract: Sulfasalazine (SSZ) is an anti-inflammatory drug that has been used to treat inflammatory bowel disease and rheumatoid arthritis for decades. Recently, some reports have suggested that SSZ also has anti-cancer properties against human tumors. However, little is known about the effects of SSZ on oral cancer. The aim of this study was to investigate the anti-cancer effects of SSZ in oral squamous cell carcinoma (OSCC) cells and to elucidate the mechanisms involved. The authors investigated the anti-proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…). It is well known that AKT suppresses both autophagy and apoptosis in addition to phosphorylating Beclin‐1 and Bad, which result in the inhibition of pro‐apoptotic and pro‐autophagic functions (Han et al, ). Our experiments showed that EGCG induced autophagy through upregulating the expression levels of Beclin‐1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…). It is well known that AKT suppresses both autophagy and apoptosis in addition to phosphorylating Beclin‐1 and Bad, which result in the inhibition of pro‐apoptotic and pro‐autophagic functions (Han et al, ). Our experiments showed that EGCG induced autophagy through upregulating the expression levels of Beclin‐1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They include epigallocatechin-3-gallate, aliphatic acetogenin, galanin receptor 1, and S-allylcysteine (56)(57)(58)(59). Certain inhibitors, including pterostilbene, astaxanthin and sulfasalazine (SSZ) (60)(61)(62), may also induce tumor cell apoptosis. Other inhibitors include those that have the potential to inhibit either oral tumor angiogenesis (for example, cetuximab) (63) or tumor invasion and metastasis (for example, vinculin, phenethyl isothiocyanate, cardiotoxin III and resveratrol) (64)(65)(66)(67).…”
Section: Regulation Of the Mapk Signaling Pathway For Targeted Oral Cmentioning
confidence: 99%
“…Drugs other than COX inhibitors have been shown to interfere with the NF-κB pathway in various malignancies, e.g., glucocorticoids, while being pro-apoptotic in leukemia and lymphomas, have been found to enhance survival of some breast cancer cell lines through promoting NF-κB transcriptional activity leading to upregulation of c- Myc and enhanced anti-apoptotic function (62, 63). Sulfasalazine can act as a NF-κB inhibitor leading to reduced proliferation and enhanced apoptosis of esophageal cancer cell lines (64) and has be shown to induce autophagic cell death in oral cancer cell lines, although this was thought to be mediated via Akt and ERK pathways (65). …”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%